Genetic fingerprinting of Theileria parva using a telomeric DNA probe - Bishop, Richard P.; Spooner, P.R.; Sohanpal, B.K. (Springer, 1996)
A cloned Theileria parva telomeric DNA sequence, designated pTpUtel, was used to characterize T. parva stocks and clones by hybridization to EcoRI-digested DNA. Eight of the nine T. parva stocks tested were discriminated by the telomeric restriction-fragment-length polymorphisms (RFLOs). Two isolates derived from buffalo 7014 by tick feeding on different occasions were also differentiated using the probe. The probe gave comparable results on purified piroplasm or schizont-infected lymphocyte DNA and did not cross-hybridize with uninfected bovine DNA. The telomeric restriction pattern of a cloned T. parva parasite remained identical after four passages through ticks and cattle. The telomeric sequence therefore represents a useful additional tool for analysis of theileriosis epidemiology.